Scalp Block Is Associated With Improved Recurrence Profiles in Patients Undergoing Primary Glioma Resection Surgery. Issue 3 (July 2021) - Sung, Chao-Hsien; Tsuang, Fon-Yih; Shih, Chung-Chih; Chang, Jui-Ling; Liao, Min-Hsiu; Yang, Ya-Wen; Lee, Tzong-Shiun; Cheng, Hsiao-Liang; Wu, Chun-Yu
Abstract : Background: Glioma is associated with high recurrence and poor survival, despite the success of tumor resection surgery. This may be partly because the immune microenvironment within a glioma is susceptible to perioperative immunosuppression. Therefore, intraoperative anesthesia-related immunomodulators, such as scalp block, intravenous anesthesia, the opioid dosage administered, and transfusions, may influence oncological outcomes among patients with glioma. The aim of this retrospective study was to investigate the influence of anesthetic techniques on oncological outcomes after craniotomy for glioma resection, particularly the effects of scalp block, intravenous anesthesia, and inhalation anesthesia. Methods: Consecutive patients who underwent primary glioma resection surgeries between January 2010 and December 2017 were analyzed to compare postcraniotomy oncological outcomes (progression-free survival [PFS] and overall survival) by using the Kaplan-Meier method and multivariate Cox regression analysis. A propensity score-matched regression analysis including prognostic covariates was also conducted to analyze the selected relevant anesthetic factors of the unmatched regression model. Results: A total of 230 patients were included in the final analysis. No analyzed anesthetic factor was associated with overall survival. Patients who received scalp block had a more favorable median (95% confidence interval [CI]) PFS (55.37 [95% CI, 12.63-62.23] vs. 14.07 [95% CI, 11.27-17.67] mo; P =0.0053). Scalp block was associated with improved PFS before (hazard ratio, 0.465; 95% CI, 0.272-0.794; P =0.0050) and after (hazard ratio, 0.367; 95% CI, 0.173-0.779; P =0.0091) propensity score-matched Cox regression analysis. By contrast, intravenous anesthesia, amount of opioid consumed, and transfusion were not associated with PFS. Conclusions: The study results suggest that the scalp block improves the recurrence profiles of patients receiving primary glioma resection. Abstract : Supplemental Digital Content is available in the text.